2002
DOI: 10.1063/1.1527230
|View full text |Cite
|
Sign up to set email alerts
|

Surface passivation of n-type crystalline Si by plasma-enhanced-chemical-vapor-deposited amorphous SiCx:H and amorphous SiCxNy:H films

Abstract: Excellent passivation of n-type crystalline silicon surface is demonstrated by means of intrinsic amorphous silicon carbide (a-SiCx:H) thin films. An optimum CH4/SiH4 ratio is determined, leading to an effective surface recombination velocity, Seff, lower than 54 cm s−1. By adding a constant flow of N2 to the precursor gases, the surface passivation is improved to Seff⩽16 cm s−1. From infrared spectroscopy measurements of these films, it can be deduced that the N2 flow increases the carbon content of the layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 17 publications
1
29
1
Order By: Relevance
“…• C. 11 These asdeposited films also possess low film density of 1.6-2.0 g/cm 3 , which can be attributed to the existence of micropores, but limited porosity, in the as-deposited SiC x N y films due to the induced pores resulting from organic phase and the formation of Si-(CH 2 ) n -Si with the matrix structure. 12 In order to explore and fabricate porous SiC x N y films with higher porosity, a sacrificial porogen, epoxycyclohexane (ECH) as illustrated in Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…• C. 11 These asdeposited films also possess low film density of 1.6-2.0 g/cm 3 , which can be attributed to the existence of micropores, but limited porosity, in the as-deposited SiC x N y films due to the induced pores resulting from organic phase and the formation of Si-(CH 2 ) n -Si with the matrix structure. 12 In order to explore and fabricate porous SiC x N y films with higher porosity, a sacrificial porogen, epoxycyclohexane (ECH) as illustrated in Fig.…”
mentioning
confidence: 99%
“…A conservative approach was proposed by Nguyen et al, 7 who prepared a dielectric barrier bilayer of dense SiN y /porous SiC x N y , exhibiting 12% porosity, by performing plasma deposition of dimethylsilacyclopentane and NH 3 and then using UV to cure the samples. The dense films of the bilayer on top helped protect the underlying copper layer against plasma-induced damage and oxidation caused by the diffusion of oxygen, whereas the bottom porous film of the bilayer contributed to a reduction in the dielectric constant.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 A number of different techniques, such as ion implantation, 3,4 chemical vapor deposition, [5][6][7][8][9][10][11][12][13][14][15][16] or sputtering, 17 among others, have been employed to obtain this material, since Gómez et al suggested the possible miscibility of ␤-Si 3 N 4 and the hypothetical one, ␤-C 3 N 4 . 18 The optical properties of SiCN suggest the behavior as a wide-bandgap semiconductor in the case of the crystalline phase, with potential applications for blue or ultraviolet optoelectronic devices.…”
mentioning
confidence: 99%